2007
DOI: 10.1197/jamia.m2114
|View full text |Cite
|
Sign up to set email alerts
|

Issues in Biomedical Research Data Management and Analysis: Needs and Barriers

Abstract: Themes identified in this study suggest that at least some common data management needs will best be served by improving access to basic level tools such that researchers can solve their own problems. Additionally, institutions and informaticians should focus on three components: 1) facilitate and encourage the use of modern data exchange models and standards, enabling researchers to leverage a common layer of interoperability and analysis; 2) improve the ability of researchers to maintain provenance of data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 24 publications
3
113
0
2
Order By: Relevance
“…Cragin et al (2010) also found that researcher attitudes towards research data sharing were colored by the amount of time it would take to prepare data for sharing. Anderson et al (2007) report that scientific communities are interested in solving these problems themselves, but lack the tools and resources to do so. This duality between skepticism of the regulatory framework for research data management and a strong sense of urgency to safeguard data is a key point in understanding how to approach research data on campus.…”
Section: Interview Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cragin et al (2010) also found that researcher attitudes towards research data sharing were colored by the amount of time it would take to prepare data for sharing. Anderson et al (2007) report that scientific communities are interested in solving these problems themselves, but lack the tools and resources to do so. This duality between skepticism of the regulatory framework for research data management and a strong sense of urgency to safeguard data is a key point in understanding how to approach research data on campus.…”
Section: Interview Resultsmentioning
confidence: 99%
“…A third option, taken by some in the literature, is to combine surveys and interviews to leverage the respective breadth and depth provided by these methods (e.g. Anderson et al, 2007;Beagrie et al, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the problems have been well documented by Anderson et al [3] in the context of biomedical research. Many of their conclusions apply in general across the biological sciences, especially at the medium sized laboratory level.…”
Section: The Data Handling Problemmentioning
confidence: 97%
“…It is inevitable for the future biomedical domain expert to switch from the classical consumer-like role [44] to an active part in the knowledge discovery process [27,30]. However, this is not so easy, because it is well known that many biomedical research projects fail due to the technical barriers that arise to the domain experts in data integration, data handling, data processing, data visualization and analysis [1,34,43]. A survey from 2012 among hospitals from Germany, Switzerland, South Africa, Lithuania, and Albania [60] showed that only 29 % of the medical professionals were familiar with any practical application of data mining methods and tools.…”
Section: Graph-based Discovery In Medical Researchmentioning
confidence: 99%